Synthesis and Properties of B(Ph)(OR) Complexes of Azadipyrrin. Issue 31 (7th August 2018) - Koch, Angira; Kumar, Sunit; Ravikanth, Mangalampalli
Abstract : The first examples of B(Ph)(OR) complexes of azadipyrrin were prepared through the treatment of azadipyrrin with BPhCl2 in the presence of water, aliphatic alcohol or aryl alcohol in toluene under reflux for 3–4 h. Simple silica gel column chromatographic purification afforded the B(Ph)(OR) complexes of the azadipyrrins in 20–40 % yields. The reactivity of the –OH group at the B III centre of the B(Ph)(OH) complex of azadipyrrin was tested through the treatment of the complex with (CH3 )3 SiCl in toluene/pyridine under reflux to afford the B(Ph)[OSi(CH3 )3 ] complex. All B(Ph)(OR) complexes of azadipyrrin were characterized by HRMS as well as 1D and 2D NMR spectroscopy, and the structure of the B(Ph)(OH) complex of azadipyrrin was determined by X‐ray crystallography. The X‐ray structure revealed that the B(Ph)(OH) complex of azadipyrrin is slightly more distorted than the BF2 complex of azadipyrrin (azaBODIPY) owing to the steric congestion at the B III centre caused by the bulkier phenyl and –OH groups. Absorption spectroscopy studies of the B(Ph)(OR) complexes of azadipyrrin indicated that the absorption bands experienced hypsochromic shifts compared with those of azaBODIPY. Electrochemical studies indicated that the B(Ph)(OR) complexes of azadipyrrin were more difficult to reduce than azaBODIPY. The B(Ph)(OR) complexes were relatively weakly fluorescent; compared with those of azaBODIPY, the fluorescence bands were hypsochromically shifted, and the quantum yields and singlet‐state lifetimes were reduced. Abstract : The stable BPh(OH) complex of 1, 3, 5, 7‐tetratolylazadipyrrin is prepared readily and used as a synthon to prepare a series of fluorescent B(Ph)(OR) complexes of azadipyrrin. The spectral and electrochemical properties of the B(Ph)(OR) complexes of azadipyrrin are also described.